A study on the non-infectious complications of continuous ambulatory peritoneal dialysis - S., Niveditha; S., Aravind; Singh, L.K. Sharatchandra (International Journal of Medical Research and Review, 2019)
Introduction: Patients with end-stage renal disease (ESRD) are treated with hemodialysis (HD) or continuous ambulatory peritoneal dialysis (CAPD).Non-infectious complications of CAPD are increasing in relative importance due to success in decreasing the rate of peritonitis. Aims and objectives: Our aim was to study the non-infectious complications in patients of ESRD on CAPD and to study the impact of the non-infectious complications in the survival of CAPD catheters. Materials and Methods: A prospective study has been conducted at Regional institute of medical science, Imphal in a total of 71patients of ESRD who are already on CAPD or newly diagnosed ESRD who have undergone CAPD catheter implantation. Their detailed history, clinical examination and relevant laboratory investigations were done and the different non-infectious complications were identified and analysed. Result: Out of the 71 patients studied 39 patients had complications like hypokalemia (15 patients), omental wrap (10 patients), catheter tip migration (6 patients), haemoperitonium (2 patients), hydrothorax (2patients), exit site leak(2patients), abdominal wall edema (1patient), catheter block(1patient). Conclusion: In our study the most common non-infectious complication was hypokalemia followed by omental wrap and catheter tip migration. Knowledge about the common prevalent non-infectious complications of CAPD alerts the treating doctor to take up the specific corrective steps at an earlier stage, thus preventing the morbidity associated with the same. We conclude that the majority of non-infectious complications in these patients were treatable and did not interfere with the catheter survival.